2019
DOI: 10.5603/gp.2019.0116
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of serum CA125 levels with ER, PR, P53 and Ki-67 expression in endometrial carcinomas

Abstract: Objectives:The present study evaluates the relationship between the expression levels of hormone receptors (HRs), Ki-67, p53 and serum cancer antigen 125 (CA125) levels in endometrial cancer and clinicopathological risk factors, and determines their prognostic values. Material and methods:This retrospective study included 49 patients with endometrial cancer whose estrogen receptor (ER) and progesterone receptor (PR) Ki-67 and p53 expression levels were determined through immunohistochemical methods, and whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…High Ki67 proliferation was observed in the non-endometrioid type endometrial cancer more in this group. The percentage of Ki67 and p53 positive cells was obtained for each case as the classification (22). Contrary to the present study, no significant relationship was found in survival.…”
Section: Discussioncontrasting
confidence: 94%
“…High Ki67 proliferation was observed in the non-endometrioid type endometrial cancer more in this group. The percentage of Ki67 and p53 positive cells was obtained for each case as the classification (22). Contrary to the present study, no significant relationship was found in survival.…”
Section: Discussioncontrasting
confidence: 94%
“…Therefore, the effect of SqD should be evaluated concurrently with Ki-67 in multivariate analysis. Some previous studies reported that a high Ki-67 index correlated with a high percentage of p53 stained immunohistochemically [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have observed the association of cell proliferation with the aggressive biological behavior of tumors of different localization [9][10][11][12], while the expression of Ki67 protein has been identified as a good predictor of recurrence and as an independent prognostic factor of survival rate [12,13].…”
Section: Discussionmentioning
confidence: 99%